2006
DOI: 10.1017/cbo9780511490477
|View full text |Cite
|
Sign up to set email alerts
|

Argument and Authority in Early Modern England

Abstract: Conal Condren offers a radical reappraisal of the character of moral and political theory in early modern England through an exploration of pervasive arguments about office. In this context he explores the significance of oath-taking and three of the major crises around oaths and offices in the seventeenth century. This fresh focus on office brings into serious question much of what has been taken for granted in the study of early modern political and moral theory concerning, for example, the interplay of ideo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…2 Conal Condren and von Friedeburg both argue that fatherland rhetoric was used either to claim an office, or to criticise the performance of the individual holding a particular office. 3 It was usually found in periods of crisis, when the policy of the prince was considered harmful to a principality and the key words associated with it were: fatherland, patriot and patria. 4 Fatherland rhetoric, then, focused on how one's love of the fatherland could justify laying claim to an "office" (officium).…”
mentioning
confidence: 99%
“…2 Conal Condren and von Friedeburg both argue that fatherland rhetoric was used either to claim an office, or to criticise the performance of the individual holding a particular office. 3 It was usually found in periods of crisis, when the policy of the prince was considered harmful to a principality and the key words associated with it were: fatherland, patriot and patria. 4 Fatherland rhetoric, then, focused on how one's love of the fatherland could justify laying claim to an "office" (officium).…”
mentioning
confidence: 99%
“…Oaths of this nature, Condren shows, announced a change in status that had already taken place. 75 They simply cemented the transition, in his example from selected mayoral candidate to mayor, but in the context of this paper, from unlicensed midwife to licensed. The provision of patient testimonials as part of the licensing process confirmed that an applicant had already assumed the role of midwife in her local community.…”
Section: Early Modern Midwives' and Office-holdingmentioning
confidence: 99%
“…65 This is not particularly unusual in early modern promissory oaths whose authority generally comes from 'faith in a pristine point of origination'. 66 The midwives' oath was part of what Enid Campbell has called a 'new legal regime' of promissory oaths of office during the sixteenth century. 67 The midwives' oath explicitly designated midwifery as an 'office', indicating the perceived importance of midwives to early modern society.…”
Section: Early Modern Midwives' and Office-holdingmentioning
confidence: 99%
“…As is evident in Dewey's seldom-read paper on Hobbes (1918), this emphasis on public office draws Dewey surprisingly close to a Hobbesian notion of representation and thereby to the tradition of office-based thinking of which Hobbes was part. Besides Hobbes, the 'ethics of office' tradition includes classic political philosophers such as Cicero (1991/44BC) and Pufendorf (1934) and has been continued in more recent sociological and historical accounts and discussions of public office-holding (Weber 1917(Weber , 1919(Weber , 1922Hennis, 2009;Condren, 2006;du Gay, 2008;Strathern, 2017; see also the recent special section on 'Office' in this journal: du Gay, 2017;Hunter, 2017;Dean, 2017). What holds this research tradition together is a practical understanding of offices as bundles of duties and virtues inscribed in the particular roles that govern the conduct of individuals, as well as an understanding of the ethics of such offices as characterised by being distinct from the personal morality of those occupying them.…”
Section: Introductionmentioning
confidence: 99%